Cancer stem cell mobilization and therapeutic targeting of the 5T4 oncofetal antigen - Richard Harrop; Eric O'Neill; Peter L. Stern (SAGE Publishing, 2019)
Cancer stem cells (CSCs) can act as the cellular drivers of tumors harnessing stem cell properties that contribute to tumorigenesis either as founder elements or by the gain of stem cell traits by the malignant cells. Thus, CSCs can self-renew and generate the cellular heterogeneity of tumors including a hierarchical organization similar to the normal tissue. While the principle tumor growth contribution is often from the non-CSC components, it is the ability of small numbers of CSCs to avoid the effects of therapeutic strategies that can contribute to recurrence after treatment. However, identifying and characterizing CSCs for therapeutic targeting is made more challenging by their cellular potency being influenced by a particular tissue niche or by the capacity of more committed cells to regain stem cell functions. This review discusses the properties of CSCs including the limitations of the available cell surface markers, the assays that document tumor initiation and clonogenicity, the roles of epithelial mesenchymal transition and molecular pathways such as Notch, Wnt, Hippo and Hedgehog. The ability to target and eliminate CSCs is thought to be critical in the search for curative cancer treatments. The oncofetal tumor-associated antigen 5T4 (TBGP) has been linked with CSC properties in several different malignancies. 5T4 has functional attributes that are relevant to the spread of tumors including through EMT, CXCR4/CXCL12, Wnt, and Hippo pathways which may all contribute through the mobilization of CSCs. There are several different immunotherapies targeting 5T4 in development including antibody-drug conjugates, antibody-targeted bacterial super-antigens, a Modified Vaccinia Ankara-basedvaccine and 5T4-directed chimeric antigen receptor T-cells. These immune therapies would have the advantage of targeting both the bulk tumor as well as mobilized CSC populations.